Amino acid modulation of gut hormone release and defining roles of GLP-1 and insulin in muscle microcirculation and metabolism in older age - Abdulla, Haitham M.A. (2018)
Background: Skeletal muscle’s role as an organ extends beyond its classical function of locomotion. It represents an important metabolic repository for both glucose and amino acids. Its responses to nutrition, ageing and hormonal intervention continue to be an area of renewed debate. In addition, the ageing process is known for its multisystemic impact on human physiology. Little is known though on its effect on gastrointestinal gut hormone release in response to amino acids stimuli.